Sistem Penyimpanan Benih Berdasarkan Kearifan Lokal Masyarakat Distrik Anggi Kabupaten Pegunungan Arfak - Astrid Ferlin E. I. Ampnir; Nouke L. Mawikere; Imam Widodo (Agrotek, 2015)
This study aims to determine how the system of seed storage by the community of Pegunungan Arfak Anggi District traditionally has been done for generations to preserve local wisdom. Results from this study are expected to provide information to the public and the government about seed storage system traditionally has been done for generations in the community Anggi. Seed storage systems in seven villages in the district Anggi is still using seed storage techniques based on local wisdom that has been done for generations. Seed storage system which is unique in the storage Anggi noken system for storing seed potatoes and pumpkin plants to store grain. In addition, seed drying is done in 2 ways, namely dried and placed near the fireplace.